Clinico-pathological features of oropharyngeal squamous cell carcinomas in Malaysia with reference to HPV infection - Yap, Lee Fah; Lai, Sook Ling; Rhodes, Anthony; Sathasivam, Hans Prakash; Abdullah, Maizaton Atmadini; Pua, Kin Choo; Rajadurai, Pathmanathan; Cheah, Phaik Leng; Thavaraj, Selvam; Robinson, Max; Paterson, Ian Charles (BMC, 2018)
Background: The incidence of oropharyngeal squamous cell carcinoma (OPSCC) has been rising in Western countries and this has been attributed to human papillomavirus (HPV) infection. p16 expression is a marker for HPV infection and p16 positive OPSCC is now recognized as a separate disease entity. There are only limited data available regarding HPV-related OPSCC in Asian countries and no data from Malaysia. Methods: We identified 60 Malaysian patients with OPSCC over a 12-year period (2004-2015) from four different hospitals in two major cities, Kuala Lumpur and Penang. The detection of HPV was carried out using p16 immunohistochemistry and high risk HPV DNA in situ hybridisation. Results: Overall, 15 (25%) tumours were p16 positive by immunohistochemistry, 10 of which were also positive for high risk HPV DNA by in situ hybridisation. By comparison, a matched cohort of UK patients had a p16 positive rate of 49%. However, between 2009 and 2015, where cases were available from all four hospitals, 13 of 37 (35%) cases were p16 positive. In our Malaysian cohort, 53% of patients were of Chinese ethnicity and 80% of the p16 positive cases were found in these patients; no Indian patients had p16 positive disease, despite representing 35% of the total cohort. Conclusion: The proportion of OPSCCs associated with HPV in Malaysia appears to be lower than in European and American cohorts and could possibly be more prevalent amongst Malaysians of Chinese ethnicity. Further, our data suggests that the burden of HPV-related OPSCC could be increasing in Malaysia. Larger cross-sectional studies of Malaysian patients are required to determine the public health implications of these preliminary findings.